The nanny's handbook to magic and managing difficult dukes - Bennett, Amy Rose (Bennett, Amy Rose. Parasol Academy, 2025)
"Emmeline Chase, 25-year-old widow and new alumna, may be more high-spirited than the Academy would like. Few graduates, however, could turn a mismanaged teleportation onto a duke's rooftop into an offer of employment. But Emmeline's circumstances, along with her desperation to support her bankrupt, incarcerated father, have made her dauntless. Which seems the primary qualification to work for expert horologist Xavier Mason, Duke of St. Lawrence, and manage his three rambunctious wards. Yet Emmeline soon discovers that the nobleman's heart-melting voice and captivating mind present an entirely different sort of trouble. She cannot risk losing her license by fraternizing with her employer. Xavier's wards have sent two nannies packing in a month thanks to frogs, firecrackers, and general mayhem. In addition, Xavier's professional reputation is on the line. He's already considered odd, with his talking raven companion and his fascination with timekeeping instead of pleasure-chasing with his peers. Charming, vivacious Emmeline seems intrigued with his quirks but Xavier must have absolute peace to design London's "King of Clocks" for Westminster Palace before the competition closes. Emmeline can no doubt restore order. As long as he doesn't fall under her spell. Yet, with a possible saboteur in their midst, and the attraction flaring between them threatening to become a deliciously disastrous distraction, a touch of magic may be required."--Page 4 of cover.